2016
DOI: 10.1021/jacs.6b05341
|View full text |Cite
|
Sign up to set email alerts
|

Plating a Dendrite-Free Lithium Anode with a Polymer/Ceramic/Polymer Sandwich Electrolyte

Abstract: A cross-linked polymer containing pendant molecules attached to the polymer framework is shown to form flexible and low-cost membranes, to be a solid Li(+) electrolyte up to 270 °C, much higher than those based on poly(ethylene oxide), to be wetted by a metallic lithium anode, and to be not decomposed by the metallic anode if the anions of the salt are blocked by a ceramic electrolyte in a polymer/ceramic membrane/polymer sandwich electrolyte (PCPSE). In this sandwich architecture, the double-layer electric fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
633
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 889 publications
(641 citation statements)
references
References 36 publications
8
633
0
Order By: Relevance
“…S10 showed that the black thin layer was (Fig. 4B), which is smaller than those of previously reported allsolid-state batteries (20). Fig.…”
Section: Significancementioning
confidence: 54%
See 1 more Smart Citation
“…S10 showed that the black thin layer was (Fig. 4B), which is smaller than those of previously reported allsolid-state batteries (20). Fig.…”
Section: Significancementioning
confidence: 54%
“…The Li/LiZr 2 (PO 4 ) 3 /Li symmetric cell was prepared by putting lithium foil on both sides of the LiZr 2 (PO 4 ) 3 pellet, and the cell was cycled with different current densities in a Land instrument. The LiFePO 4 preparation process was the same as in our previous report (20). To prepare the cathode of an all-solid-state LiFePO 4 /Li cell, the active material LiFePO 4 was mixed with carbon black, cross-linked polyethylene oxide, and LiTFSI (60:12:20:8 by weight) and ground in a mortar.…”
Section: Methodsmentioning
confidence: 99%
“…The LiFePO 4 cathode was mixed with the CPEO-LITFSI polymer to reduce the interfacial resistance between garnet electrolyte and LiFePO 4 . [9] The XRD patterns of the as-prepared Li 6.5 La 3 Zr 1.5 Ta 0.5 O 12 (LLZT) with different amounts of LiF are shown in Figure 1 a and Figure S2; all the pellets crystallize in a cubic garnet structure with high purity and the lattice parameters of all the LLZT pellets calculated by the refinement with the Fullprof software were a = 12.9340 . LiF does not enter into the LLZT grains.…”
mentioning
confidence: 99%
“…However, brittleness results in high fracture energy, and interphase contacting problems between electrolyte and lithium metal restrict practical application severely 15, 16, 17, 18, 19, 20. In comparison, polymer electrolyte improves the contact matters because of its flexibility, but the low ion conductivity under room temperature and narrow electrochemical window greatly impose restrictions on its further applications.…”
mentioning
confidence: 99%